2010
DOI: 10.1001/archsurg.2010.204
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Stroke Prevention in the Era of Carotid Stenting

Abstract: Stroke is a leading cause of morbidity and mortality worldwide. Traditional therapy for extracranial carotid artery occlusive disease, a significant risk factor for stroke, consists of optimal medical management and selective surgical treatment with carotid endarterectomy (CEA) for stroke risk reduction. Buoyed by the widespread application of percutaneous interventions for the treatment of coronary artery disease, carotid artery stenting (CAS) has steadily developed during the past decade as an alternative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…CAS is believed to prevent stroke as a less invasive alternative to carotid endarterectomy (CEA) in selected patients with symptomatic carotid stenosis [14] [15], but its influence on cognitive performance in patients remains controversial [16] [17]. The results in our study agreed with the results from previous reports which have shown improvements in cognitive function in patients treated with carotid stent placement [18]- [22].…”
Section: Discussionsupporting
confidence: 88%
“…CAS is believed to prevent stroke as a less invasive alternative to carotid endarterectomy (CEA) in selected patients with symptomatic carotid stenosis [14] [15], but its influence on cognitive performance in patients remains controversial [16] [17]. The results in our study agreed with the results from previous reports which have shown improvements in cognitive function in patients treated with carotid stent placement [18]- [22].…”
Section: Discussionsupporting
confidence: 88%
“…Several randomized trials have compared treatment modalities for carotid stenosis in the prevention of disease progression, stroke and death [16][17][18][19][20][21]. The investigators in these trials have consistently identified proper patient selection as the key to maximize benefits from each treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…3 Buoyed by advancements in endovascular therapy, carotid artery angioplasty and stenting has increased in popularity and utility, primarily for atherosclerotic occlusive disease. 4,5 However, neither an open nor endovascular approach to treat the cervical carotid artery has been reported for this rare problem because fibrosing mediastinitis, as its name indicates, is generally confined to the mediastinum. Interestingly in this case, the cervical carotid artery at the carotid bifurcation was involved by direct extension of the fibrosing mass from the mediastinum extending up the right neck.…”
Section: Discussionmentioning
confidence: 99%